2016
DOI: 10.1186/s12904-016-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

“It still haunts me whether we did the right thing”: a qualitative analysis of free text survey data on the bereavement experiences and support needs of family caregivers

Abstract: BackgroundResearch suggests that there may be bereavement experiences and support needs which are specific to family caregivers providing end of life care (EoLC), although this remains an under-researched area. This paper focuses on themes relating to bereavement which were derived from an analysis of free text survey responses collected in a research priority setting exercise for palliative and EoLC.MethodsThe priority setting exercise involved a public survey, designed to generate research priorities. Rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 32 publications
6
60
3
Order By: Relevance
“…This study confirmed the findings of many others internationally, that care-givers need support [19,37,62,75,76], often ignore their own needs [20] and bear the burden of advocacy [13,14] and guilt [38,77]. The family unit needs information [26,31,35,36,78,79] and financial help [62,80,81].…”
Section: Needs Of the Family Unitsupporting
confidence: 86%
See 3 more Smart Citations
“…This study confirmed the findings of many others internationally, that care-givers need support [19,37,62,75,76], often ignore their own needs [20] and bear the burden of advocacy [13,14] and guilt [38,77]. The family unit needs information [26,31,35,36,78,79] and financial help [62,80,81].…”
Section: Needs Of the Family Unitsupporting
confidence: 86%
“…Inadequate communication was cited by about half the participants as a major unmet need. In studies of endof-life care, this is consistently ranked as a critical need [13,14,24,38]. Poor communication was distressing to caregivers in this study.…”
Section: Communication and Attitudesmentioning
confidence: 65%
See 2 more Smart Citations
“…It is highlighted that the lack of empathy and social support, and the exclusion from religious or social rites, tend to intensify emotional reaction and to contribute to the development of complicated bereavement (20) , given that the family members' capacity in dealing with the death of their loved ones depends on their own psychological and physical conditions, but also on their support network (21) . Thus, given the lack of support, the bereaved family experiences an "emptiness", evincing the need for continuing the care after the death of their loved ones (22) , set as a risk factor for the process of elaborating the bereavement. Despite 75.4% of participants having reported not receiving social/ community support, it is believed that the spiritual/religious support, reported by 60.9% of participants, may have met this deficit.…”
Section: Discussionmentioning
confidence: 99%